Marketing in the metaverse: Moving forward – What’s next? - Cheah, Isaac; Shimul, Anwar Sadat (Routledge, 2023)
The widespread adoption of the metaverse has generated significant discussions within the marketing community about the challenges and opportunities it presents for consumer interaction with brands. This paper investigates how the metaverse may affect marketing and suggests a novel paradigm to deal with these problems. Furthermore, this article highlights new research directions. The article also offers a checklist for researchers to use when researching the potential advantages or disadvantages of the metaverse for digital marketing and advertising, branding, services, supply chain and logistics, ethics and sustainability, diversity and inclusion and consumer wellness. The proposed research agenda intends to offer insightful information to academics, practitioners, and decision-makers.